Impact of lockdown on children with type-1 diabetes: returning to the community was associated with a decrease in HbA1c - Morat, Benjamin; Lucidarme, Nadine; Gibert, Auriane; Harbulot, Carole; Lachaume, Noémie; Gréteau, Stéphanie; Basmaci, Romain (Frontiers in Pediatrics, 2023)
• Background: In March 2020, a 2-month lockdown of the entire population has been declared in France to limit the spread of COVID-19. Sudden changes in daily life can impact the glycemic control of patients with type 1 diabetes (T1D), especially children and adolescents. We aimed to assess the impact of the lockdown on glycemic control in children and adolescents with T1D. • Methods: Children with T1D were prospectively recruited in two pediatric centers from May 11 to August 1, 2020. At inclusion, patients and/or parents were asked to fill in a form assessing the patient’s lifestyle during the lockdown and a medical case report form was filled in by clinician. The mean of the three last glycated hemoglobin (HbA1c) values obtained before lockdown (HbA1c_mean; before March 17, 2020) was compared to the first HbA1c value measured after the lockdown (HbA1c_after; from May 11 to August 1, 2020). Univariable and multivariable analyses were performed, as appropriate, to identify factors associated with glycemic changes during lockdown. • Results: One-hundred-and-eighteen children and adolescents (median age was 14.1 years, 50% males) with T1D (median time from diagnosis was 4.1 years) were enrolled in the study. No significant difference was observed between medians of HbA1c_mean and HbA1c_after values (8.37% [7.88; 9.32%] versus 8.50% [7.70; 9.50%], respectively; p=0.391). Returning to the community was a protective factor (OR 0.31 [0.09-0.94]; p=0.045). Patients having increased HbA1c were more frequently in contact with a suspected case of COVID-19 (OR 9.07 [2.15-53.66]; p=0.006), whereas patients having decreased HbA1c had the feeling of increase number of hypoglycemia (OR 0.19 [0.05-0.57]; p=0.006). • Conclusion: In our patients, HbA1c before and after the lockdown was stable. In subgroup analysis, returning to the community was a protective factor. In addition, feeling of hypoglycemia was more frequent in the patients with decreased HbA1c.